Improved Electrochemical Performance of Lithium Oxygen Batteries with N-methyl-2-pyrrolidone Based Composite Polymer Electrolytes. Issue 7 (23rd April 2016) - Tokur, M.; Algul, H.; Cetinkaya, T.; Uysal, M.; Akbulut, H.
Abstract : The stability and reversibility of the electrolytes is a significant limitation for cycle life performance of Lithium oxygen (Li-O2 ) batteries. Therefore, the traditionally used ionic/liquid electrolytes need to be modified with ceramic or polymer fillers to reach stable and reversible polymer composite electrolytes. Here, to increase reversibility and stability of the N-methyl-2-pyrrodione (NMP) based electrolytes, which is known as an ideal candidate to overcome electrolyte difficulties due to its attractive properties such as low flammability, viscosity and comparatively low toxicity, polymer supported liquid composites were synthesized using poly(vinylidene fluoride) (PVDF) and polyethylene oxide (PEO) polymers and aluminum oxide (Al2 O3 ) nano ceramic powders. By preparing a suitable composite polymer electrolyte using a NMP aprotic solvent, we demonstrate a Li-O2 battery which is capable of operating over 35 cycles with a capacity of 2.54 mAh. This study proved that ionic conductivity and over potential of the cell was greatly improved with the addition of polymer and ceramic additive in NMP based electrolyte. Moreover, our composite polymer electrolytes provided highly reversible Li-O2 reaction during charging/discharging and prevented clogging of the porous structure of the cathode which is beneficial to increase the cycle performance.